2003
DOI: 10.1590/s0101-20612003000200006
|View full text |Cite
|
Sign up to set email alerts
|

Purificação parcial e caracterização bioquímica de lipase extracelular produzida por nova linhagem de Rhizopus sp.

Abstract: Ciênc. Tecnol. Aliment., Campinas, 23(2): 135-140, maio-ago. 2003 135Purificação parcial e caracterização bioquímica de lipase extracelular produzida por nova linhagem de Rhizopus sp., Pastore et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
1
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 8 publications
7
34
1
9
Order By: Relevance
“…In a global evaluation, it can be noticed that optimal temperature for lipase is in the range from 30 to 40 °C, as it was verified by Abbas et al (2002);Kolossvary (1996); Burkert (2002); Kamini et al (1998);Fadiloglu and Soylemez (1997); Freire et al (1997) and Benjamin and Pandey (2001). The optimal pH found in the present work is in agreement with the data presented by other authors, which is in the range of 5.0 to 9.0 (BURKERT, 2002;MAHADIK et al, 2004;FREIRE et al, 1997;TAN et al, 2003;ABBAS et al, 2002;KAMINI;MALA;PUVANAKRISHNAN, 1998;FADILOGLU;SOYLEMEZ, 1997;BENJAMIN;PANDEY, 2001;MARTINS, 2001;KOLOSSVÁRY, 1996;SHU;XU;LIN, 2006;PASTORE;DA COSTA;KOBLITZ, 2003).…”
Section: Characterization Of the Crude Enzymatic Extracts Obtained Ussupporting
confidence: 93%
See 1 more Smart Citation
“…In a global evaluation, it can be noticed that optimal temperature for lipase is in the range from 30 to 40 °C, as it was verified by Abbas et al (2002);Kolossvary (1996); Burkert (2002); Kamini et al (1998);Fadiloglu and Soylemez (1997); Freire et al (1997) and Benjamin and Pandey (2001). The optimal pH found in the present work is in agreement with the data presented by other authors, which is in the range of 5.0 to 9.0 (BURKERT, 2002;MAHADIK et al, 2004;FREIRE et al, 1997;TAN et al, 2003;ABBAS et al, 2002;KAMINI;MALA;PUVANAKRISHNAN, 1998;FADILOGLU;SOYLEMEZ, 1997;BENJAMIN;PANDEY, 2001;MARTINS, 2001;KOLOSSVÁRY, 1996;SHU;XU;LIN, 2006;PASTORE;DA COSTA;KOBLITZ, 2003).…”
Section: Characterization Of the Crude Enzymatic Extracts Obtained Ussupporting
confidence: 93%
“…The maximum lipase activity obtained in this design was 3.22 U.mL -1 , after 96 hours of fermentation (after the kinetic study), which is higher than that reported by Puthli et al (2006), who evaluated lipase production by Candida rugosa, obtaining a maximum activity of 1.84 U.mL -1 after 66 hours of fermentation. However, better results were found by Benjamin and Pandey (1995) , after 72 hours of fermentation), also using Candida rugosa as microorganism.…”
Section: Resultscontrasting
confidence: 64%
“…The versatility of lipases in catalyzing different kinds of reactions associated with their different specificities endows these enzymes with an important and vast application potential (Gandhi, 1997;Sharma et al, 2001;Pastore et al, 2003;Enujiugha et al, 2004;Hansan et al, 2006;Parques et al, 2006;Freire and Castilho, 2008;Yesiloglu and Baskurt, 2008;Isibilar et al, 2008;Polizelli et al, 2008). Lipases are excellent alternatives for classic chemical syntheses with industrial applications, such as in foods, detergents, oleochemicals, pharmaceuticals, fine chemistry, cosmetics and fragrances, paper pulp, leather, biosensors and lipidrich wastewater treatment (Gandhi, 1997;Paques et al, 2006;Freire and Castilho, 2008).…”
Section: Lipase Applicationsmentioning
confidence: 99%
“…Segundo Pastore et al [3], a atividade lipolítica é muito aumentada quando situada na interface polar/apolar e apresentam maior afinidade por ácidos graxos de cadeia longa. Com a técnica da difração de raios-X, foi possível obter a estrutura tridimensional de algumas lipases sendo possível deste modo, compreender melhor os fatores que determinam sua região especificidade, enantioseletividade e o mecanismo de ação.…”
Section: V De Jesus Et Al Scientia Plena 12 054208 (2016)unclassified